2019
DOI: 10.1039/c9gc01043b
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-free Suzuki–Miyaura coupling reaction of an aryl chloride using a continuous irradiation type microwave and a palladium nanoparticle catalyst: effect of a co-existing solid

Abstract: A co-existing solid, Al foil, plays a key role in ligand-free Suzuki–Miyaura coupling using SGlPd (sulfur-modified glass-supported Pd) and continuous microwave irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, from the earliest work, it was suggested that the absence of ligands could significantly enhance the catalytic activity of such surfaces . As such, a number of different approaches to stabilizing naked PdNPs have been taken, and used in Suzuki–Miyaura reactions. However, given the problems with naked PdNPs agglomerating and/or leaching, there can often be limits to the observed TONs that can be achieved using such systems. , This is distinct from some of the ligand-stabilized Pd nanoparticles discussed in the introduction to this paper. As such, there are clear needs for more effective ways of stabilizing naked PdNPs, and we reason that our gel stabilization strategy reported here is one such way of doing so.…”
Section: Resultsmentioning
confidence: 99%
“…However, from the earliest work, it was suggested that the absence of ligands could significantly enhance the catalytic activity of such surfaces . As such, a number of different approaches to stabilizing naked PdNPs have been taken, and used in Suzuki–Miyaura reactions. However, given the problems with naked PdNPs agglomerating and/or leaching, there can often be limits to the observed TONs that can be achieved using such systems. , This is distinct from some of the ligand-stabilized Pd nanoparticles discussed in the introduction to this paper. As such, there are clear needs for more effective ways of stabilizing naked PdNPs, and we reason that our gel stabilization strategy reported here is one such way of doing so.…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 107 PdNPs/KCC-1 mediated carbonylative SM cross-coupling reaction 223 In 2019, Yamada and co-workers 224 investigated the effect of a co-existing metal in the ligand-free Suzuki-Miyaura coupling reaction of an aryl chloride under continuous irradiation microwave and a PdNPs catalyst (SGlPd), and established that the co-existing metal such as aluminum foil is involved in this reaction due to its microwave absorption ability in the reaction system. Mohazzab and co-workers 225 synthesized reusable mesh-GO/Pd catalyst by immobilization of Pd NPs on stainless-steel mesh.…”
Section: Review Synopenmentioning
confidence: 99%
“…One of the most fundamental supports for metal NPs is inorganic materials such as metal oxides, clay, and so on [31][32][33]. There have been developed many highly active inorganic materials and supported metal NP catalysts, such as those which proceed the C-C bond forming reaction at room temperature [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. Typical recent examples include the following:…”
Section: Several Supports For Metal Nanoparticles 21 Inorganic Materialsmentioning
confidence: 99%